HUBUNGAN KEBIASAAN MENONTON MUKBANG, PENGETAHUAN GIZI DAN TINGKAT STRES DENGAN PERUBAHAN PERILAKU MAKAN NEGATIF PADA PENGGEMAR MUKBANG DI MEDIA SOSIAL INSTAGRAM - Amalia, Dea Sofa; Nuzrina, Rachmanida; Gifari, Nazhif; Angkasa, Dudung; Sitoayu, Laras (Journal of Nutrition College, 2021)
Background: Nowadays, Mukbang video is very popular on social media, especially Instagram, also known as an eating show which is a host doing a consumes various quantities of food. Teenager has an impressionable characteristic which can affect a person to imitate â€œnegative-eatingâ€ behaviour, such as the food-vloggers did on the Mukbang video. In general, it is because the foods on the Mukbang video do not give an attention to the ingredients itself/it tends to be higher on calories, fat, and cholesterol. In case, this â€œnegative-eatingâ€ behavior which is eating food with large portion and not balanced diet was imitated by a large part of society, then it can generate many nutrient problems that can affect to the health.Objectives: To know the relation between the behaviour of watching Mukbang, the nutrient knowledge, and the stress level with the changing of eating behaviour of Mukbang enthusiast on social media, Instagram.Methods: This research design was Cross Sectional with 125 respondents. All of the data were taken using Google Form with limited time for 10 minutes. Statistical data analysis used Chi-Square testResults: There is a significant relationship between the behaviour of watching Mukbang with the changing of negative eating behaviour (p-value = 0.003), there is a significant relationship between the nutrient knowledge with the changing of negative eating behaviour (p-value = 0.009), there is a significant relationship between the stress level with the changing of eating behaviour of Mukbang enthusiast on Instagram (p-value = 0.034).Conclusion: There is a significant relationship between the behaviour of watching Mukbang, the nutrient knowledge, and the stress level with the changing of eating behaviour of Mukbang enthusiast on Instagram. There needs to be a balance in the behaviour of watching Mukbang, the nutrient knowledge, and the stress level, in order there is no change in â€œnegative-eatingâ€ behavior